Economic Analysis of PV-Utility Grid Hybrid Electric Vehicle Charging Station in Mandalay City - Soe Soe Than; Swe, Wunna (AI Society & STMIK Indonesia, 2024)
Electric vehicles (EVs) are catching on everywhere worldwide. Building more clean energy infrastructure for EVs could help lessen greenhouse gas emissions and make city air cleaner. EVs charged with electricity from solar panels emit fewer pollutants compared to those charged with grid electricity. Therefore, combining solar power with EV charging stations could be a good way to promote sustainable development in the EV market. Despite rapid EV adoption in Mandalay, the charging infrastructure remains limited, mostly stations reliant on grid electricity. In this paper, the proposed system integrates photovoltaic technology with the existing utility grid infrastructure of EV charging station at the corner of 78th road & 101st road in Mandalay city, Myanmar. HOMER Grid is utilized to analyze the economic feasibility. The results of the proposed system describe that the cost of energy (COE) is reduced by 0.05/kWh. Additionally, the integrated system incurs fewer costs and generates more profits.